INDONESIA’S PERSPECTIVE AND POSSIBLE STRATEGIES AS THE CHAIRMANSHIP OF ASEAN 2023 IN RESPONDING TO THE EMERGENCE OF AUSTRALIA-UK-USA DEFENSE PACT - Silalahi, Alma Evelinda; Pedrason, Rodon; Hadisancoko, Rizerius Eko; Surjaatmadja, Surachman; Risdhianto, Agung; Almubaroq, Hikmat Zakky (Jurnal Pertahanan dan Bela Negara, 2023)
The formation of the AUKUS Defense Pact (Australia-UK-US) has the potential to trigger militarization and regional instability. Indonesia, poised to lead ASEAN in 2023, is concerned about the impact of heightened tensions and threats to regional security. If AUKUS alters the role of external powers in this region, the centrality of ASEAN's role in preserving regional stability could be disrupted. This study aims to analyze the perspectives and strategies that Indonesia, on behalf of ASEAN, can adopt in facing AUKUS. A qualitative research method is employed with a descriptive approach. Data collection involves comprehensive interviews and a literature review. The SWOT method is used to formulate suitable strategies and perspectives, particularly those that reaffirm ASEAN's central role. The research findings reveal that the emergence of AUKUS has triggered security dilemmas within ASEAN, accelerated regional arms races, and potentially altered the balance of military power. As ASEAN Chair in 2023, Indonesia is committed to fostering unity within ASEAN to preserve regional stability and interests. The SO strategy (Strengths-Opportunities), through diplomatic efforts, economic cooperation, and multilateralism coordinated by ASEAN, is identified as the way for Indonesia to reinforce ASEAN's central role and respond to AUKUS. Consequently, Indonesia can promote regional cooperation, stability, and resilience.